Case report: Unexpected parvovirus B19 infection in a myeloma patient treated with daratumumab - Palazzo, Marianna; Ciolli, Gaia; Pilerci, Sofia; Attucci, Irene; Pengue, Ludovica; Vannucchi, Alessandro Maria; Antonioli, Elisabetta (Frontiers in Hematology, 2022)
Multiple myeloma patients have an increased risk of infections due to both the inherent nature of the disease and ongoing treatment. We describe the case of a patient who was treated with daratumumab-lenalidomide-dexamethasone regimen for two years and developed a parvovirus B19 infection. The clinical picture, characterized by trilinear cytopenia, was initially attributed to anti-neoplastic treatment. Later on, when the patient’s condition worsened, an extensive diagnostic workup was applied and parvovirus B19 infection was detected by PCR. Due to the lack of effective antiviral drugs, the patient received IV immunoglobulins and it took 10 days to achieve a decrease in viral copies. Physicians should be aware that recent changes in the therapeutic scenario of multiple myeloma would make patients more susceptible to atypical infections in this patient setting.